Super-hydrophobic PEI / MXene / titanic acid film and preparation method thereof
Through the preparation method of superhydrophobic PEI/MXene/titanic acid film, the problems of complex and high cost of material preparation in the prior art are solved, efficient oil-water separation and stability are achieved, and the needs of industrial applications are met.
Patent Information
- Application Number
- CN202411295008.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
The existing superhydrophobic materials preparation technology is complex and costly, difficult to meet the needs of industrial applications, and it performs poorly in oil-water separation efficiency and selectivity, especially in terms of long-term stability and anti-blocking ability.
Using the preparation method of superhydrophobic PEI/MXene/titanic acid film, the PEI/MXene film was spin-coated to form the PEI/MXene film and surface roughening and Titanate nanowires are grown and finally superhydrophobic groups are modified and stabilized to form a superhydrophobic film with excellent separation performance.
It achieves low-cost and efficient oil-water separation performance, enhances the separation efficiency and selectivity of membrane materials, and maintains stability and durability under different environmental conditions, making it suitable for industrial applications.
Smart Images

Figure HDA0005045669140000011 
Figure HDA0005045669140000012 
Figure HDA0005045669140000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional film materials, and in particular to a super-hydrophobic PEI / MXene / titanic acid film and a preparation method thereof. Background Art
[0002] Regulating the hydrophilic and hydrophobic properties of material surfaces is a key direction in the field of surface chemistry. This property plays a vital role in many fields, including corrosion resistance, waterproofing and antifouling, heat transfer, oil-water separation, and biomedicine. The superhydrophobic surface properties exhibited by plants such as lotus leaves in nature provide a valuable reference for the design of artificial material surfaces. By introducing micro-nano structures on the surface of materials and modifying them with superhydrophobic groups, these natural phenomena can be effectively simulated to achieve superhydrophobic and oleophilic properties on the surface of materials. However, existing surface micro-nanostructure preparation technologies, such as laser micromachining, high-temperature in-situ oxidation, chemical vapor deposition, hydrothermal or solution thermal reactions, often involve high temperature and high pressure conditions, expensive equipment, or complex chemical reagents. These factors make the preparation process complicated and costly, and it is difficult to fully meet the actual needs of industrial applications.
[0003] In the preparation of super-hydrophobic materials, traditional methods often use zero-dimensional or one-dimensional nanostructures to increase surface roughness, which plays a certain role in forming super-hydrophobicity. However, these structures may have problems of insufficient stability and selectivity in practical applications. For example, the technology described in patent CN107715699A, although successfully integrating photocatalysis and ultrafiltration functions, its preparation process is relatively complicated, and the efficiency and selectivity in applications such as oil-water separation need to be further improved. In addition, existing oil-water separation technologies, especially separation methods based on membrane materials, although they can achieve a certain degree of separation effect, their performance in efficiency and anti-clogging ability is not ideal, and these problems limit the potential of membrane technology in a wider range of applications. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a super-hydrophobic PEI / MXene / titanic acid membrane to solve the technical problem that the existing material preparation technology is difficult to balance cost-effectiveness and efficient oil-water separation performance. Traditional methods often rely on complex processes and expensive equipment when preparing super-hydrophobic materials, which not only increases production costs, but also limits their widespread adoption in industrial applications. At the same time, the performance of existing materials in terms of oil-water separation efficiency and selectivity is not ideal, especially in terms of long-term stability and anti-clogging ability. The present invention aims to achieve a super-hydrophobic membrane that is both economical and efficient and has excellent separation performance through an innovative preparation method to meet the growing industrial needs.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A method for preparing a super-hydrophobic PEI / MXene / titanic acid film, the preparation method comprising the following steps:
[0007] S1: Mix and stir two-dimensional Ti3C2 MXene powder, polyetherimide (PEI) powder and N-methylpyrrolidone (NMP) solution to form a uniform slurry;
[0008] S2: Spin-coat the slurry obtained in step S1 on a substrate and immerse it in deionized water for 24 hours to form a PEI / MXene film;
[0009] S3: performing surface roughening treatment on the PEI / MXene film obtained in step S2 to expose the MXene surface;
[0010] S4: immersing the PEI / MXene film roughened in step S3 into a hydrogen peroxide reaction system to grow titanate nanowires;
[0011] S5: performing super-hydrophobic group modification and stabilization treatment on the surface of the composite membrane after the reaction in step S4 to form a super-hydrophobic surface, and finally obtaining the super-hydrophobic PEI / MXene / titanic acid membrane.
[0012] As a preferred technical solution, the mass ratio of the two-dimensional Ti3C2 MXene powder and PEI powder to the N-methylpyrrolidone solution is 0.3-0.4:8-12:30.
[0013] As a preferred technical solution, the specific operation of the surface roughening treatment is to immerse the PEI / MXene film in an N-methylpyrrolidone solution preheated to a certain temperature for a certain period of time.
[0014] As a preferred technical solution, the super hydrophobic group modification is specifically surface treatment using trialkoxysilane.
[0015] As a preferred technical solution, the trialkoxysilane is at least one of octyltrimethoxysilane, dodecyltrimethoxysilane, methyltrimethoxysilane, and 1H, 1H, 2H, 2H perfluoroalkyltriethoxysilane. A further preferred technical solution is that the trialkoxysilane is octyltrimethoxysilane.
[0016] As a preferred technical solution, the stabilization treatment specifically involves heat treating the composite membrane modified with super-hydrophobic groups at 130-150° C. for a certain period of time.
[0017] As a preferred technical solution, the hydrogen peroxide reaction system is a mixed reaction liquid composed of hydrogen peroxide solution, concentrated nitric acid and melamine. As a preferred technical solution, the volume mass ratio of the hydrogen peroxide solution, concentrated nitric acid and melamine is 150-250 (mL): 2-5 (mL): 80-120 (mg), and the mass concentration of hydrogen peroxide in the hydrogen peroxide solution is 25-35wt.%.
[0018] Another aspect of the present invention is to provide a super hydrophobic PEI / MXene / titanic acid film, wherein the PEI / MXene / titanic acid film is prepared by the above-mentioned super hydrophobic PEI / MXene / titanic acid film preparation method, wherein the water contact angle of the PEI / MXene / titanic acid film is greater than 160°.
[0019] Beneficial effects of the present invention:
[0020] The preparation method of the super-hydrophobic PEI / MXene / titanic acid membrane of the present invention innovatively combines the unique physical and chemical properties of two-dimensional Ti3C2 MXene with the structural advantages of one-dimensional titanic acid nanowires, not only realizing the super-hydrophobic properties of the PEI material surface, but also optimizing the internal porous structure, allowing oil molecules to pass through effectively. This design not only enhances the separation efficiency and selectivity of the membrane material, but also maintains its stability and durability under different environmental conditions, which helps to improve the application performance of oil-water separation and oil extraction in oil-water mixtures.
[0021] In addition, the preparation method of the super-hydrophobic PEI / MXene / titanic acid film of the present invention helps to achieve low-cost and high-efficiency large-scale production through a simplified process flow and the conditions without high temperature and high pressure equipment. The preparation method of the present invention is operated at room temperature or mild temperature, is easy to control, and at the same time ensures the uniformity of the microscopic morphology of the obtained composite membrane material and the excellence of the super-hydrophobic performance, and the pure water contact angle is greater than 160 degrees.
[0022] In general, the super-hydrophobic PEI / MXene / titanic acid membrane of the present invention not only has excellent surface super-hydrophobicity and internal porosity, but also ensures its long-term durability and stability in industrial applications. It has strong overall comprehensive performance and environmental adaptability, can meet the stringent requirements of material performance in the fields of oil-water separation and super-hydrophobic and oleophilic, and has important application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a process flow chart of the preparation method of super-hydrophobic PEI / MXene / titanic acid film in Example 1 of the present invention.
[0024] Figure 2 This is a scanning electron microscope photograph of the PEI / MXene membrane after roughening in step S3 of Example 1 of the present invention.
[0025] Figure 3 This is a scanning electron microscope photograph of the PEI / MXene film with titanate nanowires deposited on the surface in step S4 of Example 1 of the present invention.
[0026] Figure 4 This is an X-ray diffractometer photograph of the PEI / MXene film with titanate nanowires deposited on the surface in step S4 of Example 1 of the present invention.
[0027] Figure 5 Schematic diagram of the pure water contact angle of the superhydrophobic PEI / MXene / titanic acid film prepared in Example 1 of the present invention.
[0028] Figure 6 Schematic diagram of the hydrophobic properties of the super-hydrophobic PEI / MXene / titanic acid film prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0030] Example 1
[0031] The preparation method of the super-hydrophobic PEI / MXene / titanic acid film in this embodiment has the following process flow: Figure 1 As shown, the specific steps include:
[0032] S1: 0.35 g of two-dimensional Ti3C2 MXene powder, 10 g of polyetherimide (PEI) powder and 30 ml of N-methylpyrrolidone (NMP) solution were added into a beaker and mixed with a magnetic stirrer at 80 °C for 8 h to form a uniform milky white viscous slurry.
[0033] S2: drip the milky white viscous slurry obtained in step S1 onto the substrate, and use a coating machine to spin coat at a rate of 1000 rpm for 30 seconds. After immersing the substrate covered with the slurry in deionized water for 24 hours, the film peeled off from the substrate surface is placed in the air to dry to obtain a PEI / MXene film; the substrate is a 5×5 cm 2 The glass slide was ultrasonically cleaned with ethanol and deionized water for 10 minutes respectively, and then dried in an oven at 60°C to obtain a clean glass slide.
[0034] S3: The PEI / MXene membrane obtained in step S2 is immersed in a NMP solution preheated to 50°C for 4 seconds, and then immediately immersed in deionized water to clean it to expose the MXene surface, thereby obtaining a roughened PEI / MXene membrane with a microscopic morphology as shown in FIG. Figure 2 shown.
[0035] S4: The PEI / MXene film roughened in step S3 is immersed in a hydrogen peroxide reaction system, and reacted in an oven at 80°C for 48 hours to grow titanate nanowires, thereby obtaining a PEI / MXene film with titanate nanowires deposited on the surface, which is abbreviated as H2Ti5O 11 / PEI / MXene film; the film after the reaction was completed was taken out, washed with deionized water, and dried at 60°C. Its microscopic morphology is as follows Figure 3 The X-ray diffraction pattern is shown in Figure 4 As shown; the hydrogen peroxide reaction system is a mixed reaction liquid consisting of 50 ml of hydrogen peroxide solution (mass concentration is 30 wt.%), 1 ml of concentrated nitric acid and 60 mg of melamine.
[0036] S5: The PEI / MXene film after the reaction in step S4 is placed in a 1 vol% octyltrimethoxysilane methanol solution for 1 hour, then taken out and placed in a muffle furnace for heat treatment at 140°C for 1 hour to complete the surface super-hydrophobic group modification and stabilization treatment to form a super-hydrophobic surface, and finally obtain the super-hydrophobic PEI / MXene / titanic acid film. The pure water contact angle is tested to be 165 degrees, which has excellent hydrophobic properties, such as Figure 5 and Figure 6 shown.
[0037] The super-hydrophobic PEI / MXene / titanic acid membrane prepared in this example was used to test its oil absorption capacity. 10 ml of edible oil was added to a beaker and its mass was weighed. The membrane prepared in this example was immersed in it for 1 min, then taken out and allowed to stand until no oil drops fell on its surface. The remaining oil and the mass of the beaker were weighed, and the mass of the oil absorbed by the super-hydrophobic membrane was subtracted from each other. The mass was divided by the area of the membrane to obtain the oil absorption capacity of the membrane, which was 25.9 mg / cm 2 The oil absorption capacity of the membrane was 3.45 g / g by mass.
[0038] Example 2
[0039] The raw material composition and preparation steps of the super-hydrophobic PEI / MXene / titanic acid film of this embodiment are basically the same as those of Example 1, except that in the preparation method of this embodiment, 5×5 cm 2 The glass piece is replaced with 10×10cm 2 The glass slide was used for the enlargement experiment. The hydrogen peroxide solution (mass concentration of 30 wt.%) in step S4 of Example 1 was enlarged to 200 ml, the concentrated nitric acid was enlarged to 4 ml, and the melamine was enlarged to 100 mg.
[0040] The test results show that the pure water contact angle of the superhydrophobic PEI / MXene / titanic acid film of this embodiment is 162 degrees.
[0041] The super-hydrophobic PEI / MXene / titanic acid membrane prepared in this example was used to test its oil absorption capacity. 10 ml of edible oil was added to a beaker and its mass was weighed. The membrane prepared in this example was immersed in it for 1 min, then taken out and allowed to stand until no oil drops fell on its surface. The remaining oil and the mass of the beaker were weighed, and the mass of the oil absorbed by the super-hydrophobic membrane was subtracted from each other. The mass was divided by the area of the membrane to obtain the oil absorption capacity of the membrane, which was 24.7 mg / cm 2 The oil absorption capacity of the membrane was 3.29 g / g by mass.
[0042] Example 3
[0043] The raw material composition and preparation steps of the super-hydrophobic PEI / MXene / titanic acid film of this embodiment are basically the same as those of Example 1, except that, in the preparation method of this embodiment, the immersion time in step S3 of Example 1 is extended to 5 seconds. The reaction time in step S4 is extended to 72 hours, and the rest remains unchanged.
[0044] The test results show that the pure water contact angle of the superhydrophobic PEI / MXene / titanic acid film of this embodiment is 164 degrees.
[0045] The super-hydrophobic PEI / MXene / titanic acid membrane prepared in this example was used to test its oil absorption capacity. 10 ml of edible oil was added to a beaker and its mass was weighed. The membrane prepared in this example was immersed in it for 1 min, then taken out and allowed to stand until no oil drops fell on its surface. The remaining oil and the mass of the beaker were weighed, and the mass of the oil absorbed by the super-hydrophobic membrane was subtracted from each other. The mass was divided by the area of the membrane to obtain the oil absorption capacity of the membrane, which was 26.1 mg / cm 2 The oil absorption capacity of the membrane was 3.48 g / g by mass.
[0046] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.
Claims
1. A method for preparing a super-hydrophobic PEI / MXene / titanic acid film, characterized in that: The preparation method comprises the following steps: S1: Mix and stir two-dimensional Ti3C2 Mxene powder, polyetherimide powder and N-methylpyrrolidone solution to form a uniform slurry; S2: Spin-coat the slurry obtained in step S1 on a substrate and immerse it in deionized water for 24 hours to form a PEI / MXene film; S3: performing surface roughening treatment on the PEI / MXene film obtained in step S2 to expose the MXene surface; S4: immersing the PEI / MXene film roughened in step S3 into a hydrogen peroxide reaction system to grow titanate nanowires; S5: performing super-hydrophobic group modification and stabilization treatment on the surface of the composite membrane after the reaction in step S4 to form a super-hydrophobic surface, and finally obtaining the super-hydrophobic PEI / MXene / titanic acid membrane.
2. The method for preparing a super-hydrophobic PEI / MXene / titanic acid film according to claim 1, characterized in that: The mass ratio of the two-dimensional Ti3C2Mxene powder and PEI powder to the N-methylpyrrolidone solution is 0.3-0.4:8-12:
30.
3. The method for preparing a super-hydrophobic PEI / MXene / titanic acid film according to claim 1, characterized in that: The specific operation of the surface roughening treatment is to immerse the PEI / MXene film in an N-methylpyrrolidone solution preheated to a certain temperature for a certain period of time.
4. The method for preparing a super-hydrophobic PEI / MXene / titanic acid film according to claim 1, characterized in that: The super hydrophobic group modification is specifically surface treatment using trialkoxysilane.
5. The method for preparing a super-hydrophobic PEI / MXene / titanic acid film according to claim 4, characterized in that: The trialkoxysilane is at least one of octyltrimethoxysilane, dodecyltrimethoxysilane, methyltrimethoxysilane, and 1H, 1H, 2H, 2H perfluoroalkyltriethoxysilane.
6. The method for preparing a super-hydrophobic PEI / MXene / titanic acid film according to claim 1, characterized in that: The stabilization treatment specifically involves heat treating the composite membrane modified with the super-hydrophobic group at 130-150° C. for a certain period of time.
7. The method for preparing a super-hydrophobic PEI / MXene / titanic acid film according to claim 1, characterized in that: The hydrogen peroxide reaction system is a mixed reaction liquid consisting of a hydrogen peroxide solution, concentrated nitric acid and melamine.
8. A super-hydrophobic PEI / MXene / titanic acid film, characterized in that: The PEI / MXene / titanic acid film is prepared by the method for preparing a super-hydrophobic PEI / MXene / titanic acid film according to any one of claims 1 to 7, wherein the water contact angle of the PEI / MXene / titanic acid film is greater than 160°.
